Razões da escravidão : história, historiografia e mitos - Ferreira, Hemerson Josias da Silva (2007)
This work focuses on myths used by slavers and his intellectuals to justify and to defend the slavery, presented since the first texts, articles and books appeared in the Seniority up to more recent historiographic works produced in Brazil by the end of the 20th century, analyzing as some writers understood and described the slavery and which arguments, theories, discourses and especially the principal myths used by them persisted until the early 1990s